Book reviews.
Beyond dispute-The Invention of Team Syntegrity, by Stafford Beer. Reviewed by Lew Perren
Target costing-State of the Art Review, by Peter Horvath, S. Niemand and M. Wolbold. Reviewed by Aidan Berry and Guy Blomfield.
What is Strategy-and does it matter?, by R. Whittington. Reviewed by Paul Gardiner